Photoluminescence mechanism of carbon dots: triggering high-color-purity red fluorescence emission through edge amino protonation - Qing Zhang (Nature Portfolio, 2021)
Carbon dots have garnered great interest due to their optical properties, however, engineering of the optical properties remains a challenge. Here, Zhang et al. produce carbon dots with a high color purity, providing a useful approach for engineering the optical properties of carbon dots.